2014
DOI: 10.1039/c3nr05365b
|View full text |Cite
|
Sign up to set email alerts
|

An on-demand four-way junction DNAzyme nanoswitch driven by inosine-based partial strand displacement

Abstract: A DNA four-way junction device capable of junction expansion and contraction cycles using an inosine-based partial strand displacement scheme is reported. These nanoscale positioning capabilities are used to provide on-demand activation and deactivation of a pair of split E6 DNAzymes on the device. The device also demonstrates a combined catalytic rate significantly higher than the original E6 DNAzyme under similar operational conditions. This approach can provide structural organization and spatially control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Methylation-associated DNA editing (MADE) alters the conventional double helix by replacing Watson–Crick base pairs with less energetically efficient noncanonical base pairing, creating nucleotide mismatches and nucleotide evictions at selected sites (Lee J, Hwang M, Landon PB, Lal R, Glinsky GV, in preparation). Recent experiments have shown that structural changes of DNA sequences resembling MADE markedly enhance the responsiveness of DNA to invading DNA and noncoding RNA molecules (Lee J, Hwang M, Landon PB, Lal R, Glinsky GV, in preparation) and these properties of “edited” DNA double helix can be exploited to engineer next-generation nanosensors, DNAzymes, and DNA motors ( Glinsky 2013 ; Landon et al 2014 ; Mo et al 2014 ). Invading RNAs induce a thermodynamically stable partial strand displacement state (PSDS), which may persist indefinitely as triple-stranded complexes (TSC) comprising RNA/DNA hybrids and single-stranded DNA chains.…”
Section: Resultsmentioning
confidence: 99%
“…Methylation-associated DNA editing (MADE) alters the conventional double helix by replacing Watson–Crick base pairs with less energetically efficient noncanonical base pairing, creating nucleotide mismatches and nucleotide evictions at selected sites (Lee J, Hwang M, Landon PB, Lal R, Glinsky GV, in preparation). Recent experiments have shown that structural changes of DNA sequences resembling MADE markedly enhance the responsiveness of DNA to invading DNA and noncoding RNA molecules (Lee J, Hwang M, Landon PB, Lal R, Glinsky GV, in preparation) and these properties of “edited” DNA double helix can be exploited to engineer next-generation nanosensors, DNAzymes, and DNA motors ( Glinsky 2013 ; Landon et al 2014 ; Mo et al 2014 ). Invading RNAs induce a thermodynamically stable partial strand displacement state (PSDS), which may persist indefinitely as triple-stranded complexes (TSC) comprising RNA/DNA hybrids and single-stranded DNA chains.…”
Section: Resultsmentioning
confidence: 99%
“…The newly introduced strand with higher affinity to one strand in the initial double helix displaces the other strand with lower affinity. Additionally, inosine or RNA can be used to control kinetics or Gibbs free energy of hybridization (19)(20)(21)(22). Strand displacement has been a core technique in DNA nanomanipulation for over 20 years and has been used in several mechanical nanomachines (23), logic gates (24), and sensors (19,25).…”
mentioning
confidence: 99%
“…Nanobowls can then be capped with a sphere made of biocompatible materials, including PLGA 29 , liposomes, 30 and chitosan 31 . For conditional and controlled release of the therapeutic from the bowl, such a cap could be released by specific interaction with DNA 32, 33 , enzymatic processes, or environmental triggers like temperature and pH. Existing delivery systems usually have pores or open surfaces that allow passive and/or continuous release of their loads (imaging contrast molecules or therapeutic agents).…”
Section: Resultsmentioning
confidence: 99%